Comparison of Periarticular Infiltration and Combination Delivery of Local Anesthetics for Reducing Pain and Opioid Consumption after Total Knee Arthroplasty - Ward, Derek T.; Grotkopp, Eva; Detch, Robert C.; Kim, Hubert T.; Kuo, Alfred C. (The Journal of Knee Surgery, 2020)
Surgical-site delivery of local anesthetics decreases pain and opioid consumption after total knee arthroplasty (TKA). The optimal route of administration is unknown. We compared local anesthetic delivery using periarticular soft-tissue infiltration to delivery using a combination of preimplantation immersion and intra-articular injection (combination treatment). The records of patients who underwent unilateral, cemented, primary TKA with spinal anesthesia and adductor canal blocks at a single Veterans Affairs Medical Center were retrospectively reviewed. Three subgroups were compared, including controls who did not receive additional local anesthetics, patients who received periarticular infiltration, and patients who received combination treatment. Mean daily pain scores and mean 24-hour opioid consumption on postoperative days (PODs) 0 and 1 were calculated, and analysis of variance was used to assess for significant differences. Factors that were associated with lower pain scores and opioid consumption were then identified using multivariate stepwise regression. There were 26 controls, 25 periarticular infiltration patients, and 39 combination patients. The periarticular infiltration cohort had significantly lower mean pain scores and opioid consumption than controls on POD 0, but not on POD 1. The combination cohort had significantly lower mean pain scores and opioid consumption than controls on PODs 0 and 1. There were no significant differences between the infiltration and combination groups on either day. Multivariate regression analysis showed that infiltration was associated with significantly decreased opioid consumption on both days and decreased pain on POD 0. Combination treatment was associated with significantly decreased pain and opioid consumption on both days. Both local anesthetic periarticular infiltration and combination treatment are associated with decreased pain and opioid consumption after TKA. The stronger effects of the combination treatment compared with periarticular infiltration on POD 1 suggests that combination delivery may have a longer duration of action.
Keywords: total knee arthroplasty; local anesthetic; periarticular infiltration; opioid; pain